Utility of positron emission tomography in pediatric oncology - Kula, Zbigniew; Szafrańska-Komarowska, Ineza; Małkowski, Bogdan (Contemporary Oncology/Współczesna Onkologia, 2011)
Positron emission tomography (PET) is a novel, non-invasive function imaging method that is increasingly used for the primary staging of malignant diseases, detection of recurrence and assessment of therapeutic response. The combination of PET and computed tomography (PET/CT) improves the diagnostic capability of the method. The aim of this review is to present concisely the use of PET/CT in the pediatric oncology diagnostics. In the following chapters the author discusses the indication to the PET/CT examination according to the present knowledge and prospects of the PET development. PET/CT imaging can be effectively helpful for other useful diagnostic methods with are used in pediatric oncology. In Poland application of PET/CT should find wider use especially in children with lymphomas, central nervois system tumors, neuroblastoma, Wilms tumor, bone and soft tissue tumors.